From an ethics ‘side dish’ to ‘your modus operandi’: neurotechnology researcher perspectives on the impacts of a decade of embedded ethics collaboration - Paul A. Tubig; Timothy E. Brown; Darcy McCusker; Michelle Pham; Eran Klein; Sara Goering (Journal of Responsible Innovation)
In this paper, we discuss ethics integration and consider questions about evaluating the success of such efforts by reporting qualitative data from an interview study with researchers who were part of a ten-year, multi-institutional NSF-funded neural engineering research center with a multimodal ethics integration effort. Our analysis of these data highlights three key themes from scientific collaborators about the impact of ethics integration: (1) the development of an ethical culture and expectation for ethics integration throughout the research and design process; (2) the usefulness of offering different modes of ethics engagement to foster productive collaborations between ethicists and researchers; and (3) the fostering of ethics capacity development within scientists themselves. We also report on researchers’ perspectives on the challenges of measuring the effectiveness of ethics integration.